Penerapan Metode User Centered Design Pada Rancang Bangun Sistem Penjualan Berbasis E-Commerce: Studi Kasus Toko Martijo 123 - Armyta Megasari; Suhartini Suhartini; Muchlis Muchlis (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
The rapid growth of the E-Commerce market in Indonesia is indeed beyond doubt. With the number of internet users reaching 82 million or around 30% of the total population in Indonesia, the E-Commerce market is a gold mine which is very tempting for some people who can see the potential in the future. E-Commerce is a form of changing patterns of interaction between sellers and buyers from direct physical contact and face-to-face to internet-based. With the stages of the User Centered Design method In this paper, the author uses the UML modeling language (Unifield Modeling Language) as a system design tool. From the system testing that has been done, the results displayed by the system when executed are in accordance with the design of the proposed system and interface system. with that stated the sales system has been successfully created in order to be able to help the Shop and Consumers to make the process of buying and selling online. The results of the study show that by identifying business needs, E-Commerce-based sales systems can provide more interesting information features that can meet customer satisfaction. These features include search products, account information, shipping and payment confirmation. Another important factor is trust. In this process trust is the main capital. Because without the trust of both parties, the process of buying and selling E-Commerce can occur and be carried out.